IDENTIFIKASI GERAKAN TANAH DI DAERAH TINATAH KECAMATAN ALIAN–KEBUMEN - Nur, Arief Mustofa (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2010)
Land movements in Tinatah, Alian District–Kebumen occured since 2005. Ap-proximately 40 families from 80 families are in high risk when rapid landslides occur in this area. The aim of this study is to identified the high risk and relatively safe areas. The used method was by field survey to obtain natural conditional data, landslide indications, range finder measured to local topographic map, laboratory analysis of engineering properties of soils, and evaluation of potential landslide. The study finds land movements in Tinatah area were caused by lithology of marl-claystone, structural geology of trace of anticline and fault. The low of slope causing land movement very slow with creeping type. The highest risk area is the trace of anticline with marl-claystone lithology (RT 6 RW 2). The more stable locations are the location with calcarenite lithology (RT 8 RW 2) and andesite breccia (Kalinanas). Anticipatory steps that can be done by stabilize of slope, drainage regulation, socialization, relocation to more stable places.